Budaya Organisasi Madrasah dan Kinerja Guru di MTs Insan Cendekia Sangatta Kab. Kutai Timur - Anwar Arifin; Ajahari Ajahari; Misbah Misbah; Asmawati Asmawati; Puspita Puspita; Andriana Gaffar,; Arman Paramansyah (LPPM Institut Nasional Laa Roiba Bogor, 2023)
Madrasas are part of an educational organization that organizes education with Islamic characteristics. Madrasas continue to innovate and reform in their implementation, so that they become educational institutions that have advantages and are able to compete in the midst of globalization. the performance of teachers and the culture of the madrasa organization which is reflected in aspects of values and norms that are believed to be true, attitudes and behavior of madrasa residents, as well as all habits and traditions that are internalized with existing educational programs in madrasas. The purpose of this study is to describe the organizational culture of madrasas by referring to theoretical concepts, descriptive analysis in an effort to improve teacher performance. The method in this study uses a qualitative approach. Data mining techniques through, documentation, interviews, and observation. Data is presented with a qualitative descriptive analysis. Respondents and informants in this study were madrasah heads and teachers at Madrasah Tsanawiyah Insan Cendekia Sangatta. The results of this study describe that the data that the researchers obtained from the results of observations, interviews and documentation related to the title of the study under study, namely